The Effect of Mangiferin Against Brain Damage Caused by Oxidative Stress and Inflammation Induced by Doxorubicin - Soni Siswanto; Wawaimuli Arozal; Vetnizah Juniantito; Agatha Grace; Femmi Dwinda Agustini; . Nafrialdi (Bogor Agricultural University, Indonesia, 2016)
Doxorubicin (DOX) is an anthracycline antibiotic used for anticancer therapy. However, this agent can cause various systemic side effects including cognitive impairments in chronic use. Brain damage due to DOX is caused by an increase of tumor necrosis factor-alpha (TNF-α) level in the brain. Increased TNF-α can further lead to chronic inflammation which can lead to neuronal deaths or neurodegenerative diseases. Mangiferin (MAG), a compound extracted from Mangifera indica, has been found neuroprotective activities, but its effect on DOX-induced brain damage is unknown. This study aims to determine the effect of MAG on brain damage induced by DOX. Male Sprague-Dawley rats were induced by DOX intraperitoneally. MAG was given orally at the doses of 30 and 60 mg/kg bw for 7 consecutive weeks. The parameters measured were inflammatory and oxidative stress markers in brain tissue. Coadministration of MAG with DOX reduced inflammation which was marked by the reduction of TNF-α mRNA expression, decreased TNF-α level and reduction of oxidative stress marked by increase of superoxide dismutase level and decrease of malondialdehyde level. In conclusion, MAG was shown to have a neuroprotective effect on brain damage induced by DOX, partly due to inhibition of inflammation and oxidative stress.